2021
DOI: 10.7554/elife.59755
|View full text |Cite
|
Sign up to set email alerts
|

Model-based spatial-temporal mapping of opisthorchiasis in endemic countries of Southeast Asia

Abstract: Opisthorchiasis is an overlooked danger to Southeast Asia. High-resolution disease risk maps are critical but have not been available for Southeast Asia. Georeferenced disease data and potential influencing factor data were collected through a systematic review of literatures and open-access databases, respectively. Bayesian spatial-temporal joint models were developed to analyze both point- and area-level disease data, within a logit regression in combination of potential influencing factors and spatial-tempo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…We identified several socioeconomic and environmental predictors significantly related with C. sinensis infection, which may provide insights in prevention and control of the disease. We found that community-based surveys were tended to report higher prevalence than that in schoolchildren, in line with the results of previous studies ( Lee et al, 1994a, 1994b; Min et al, 2002; Zhao et al, 2021 ). Some studies suggested that the youth eat raw fish far less frequently than the elderly, resulting in a generally lower prevalence among the youth ( June et al, 2013; Lee et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We identified several socioeconomic and environmental predictors significantly related with C. sinensis infection, which may provide insights in prevention and control of the disease. We found that community-based surveys were tended to report higher prevalence than that in schoolchildren, in line with the results of previous studies ( Lee et al, 1994a, 1994b; Min et al, 2002; Zhao et al, 2021 ). Some studies suggested that the youth eat raw fish far less frequently than the elderly, resulting in a generally lower prevalence among the youth ( June et al, 2013; Lee et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…The national surveys mainly reported raw overall prevalence by calculating the proportion of positive individuals among all examined ones ( Korea Centers for Disease Control and Prevention and Korea National Institute of Health, 2013 ), which may be influenced by sampling framework ( Mitani et al, 2021; Zhao et al, 2021 ). Differently, our estimates relied on rigorous Bayesian geostatistical modeling of all available geo-referenced disease survey data along with important environmental and socioeconomic predictors, thus was able to take into account high-resolution spatial heterogeneous of both disease infection risk and population density across the country when compiling country-level prevalence ( Lai et al, 2019; Zhao et al, 2021 ). We did not provide estimates of infection risk for islands Jeju-do and Ulleung-gun, as sparse geo-referenced data were obtained, and they are quite a distance away from the continent of South Korea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Opisthorchiasis and clonorchiasis are infections caused by the consumption of freshwater cyprinid fishes that carry the encysted metacercaria in their flesh or under their scales (Hung et al, 2013;Nithikathkul et al, 2021). Opisthorchiasis in the Asia-pacific region is caused by Opisthorchis viverrini and O. felineus (Sithithaworn et al, 2012;Waikagul et al, 2015;Xin et al, 2020;Zhao et al, 2021). The former is endemic in the Mekong River basin in Cambodia, Lao PDR, and northern Thailand (Waikagul et al, 2015;Phupiewkham et al, 2021;Kitphati et al, 2021).…”
Section: Opisthorchiasis and Clonorchiasismentioning
confidence: 99%